Application of Discovery Learning Model to Student Learning Outcomes on Chemical Equilibrium Subject at MAN Banggai Laut - Ahdiat, Mohammad; Rahmawati, Sitti; Afadil, Afadil; Suherman, Suherman; Asmita, Asmita (Universitas Lampung, 2024)
This study aims to determine and describe the influence of the discovery learning model on student learning outcomes on the subject of chemical equilibrium. This research is descriptive type. The sample used was 16 class XI students, consisting of 6 male students and 10 female students. The instruments used are lesson plans, student worksheets, teacher and student activity observation sheets, and student learning outcomes tests. Data collection techniques were carried out through teacher and student activity observation sheets and learning outcomes tests. The data that has been collected is analyzed using descriptive analysis. The results of data processing and analysis on the application of the discovery learning model on chemical equilibrium subjects obtained teacher activity with an average of 82.38% and student activity with an average of 80.19%, including in the good category. The value of student learning outcomes (cognitive, affective, and psychomotor aspects) has an average of 74, and a learning effectiveness of 75% (minimum achievement criteria: 70). Based on the results of the study, it can be concluded that learning by using the discovery learning model can improve students learning outcomes.Keywords: Discovery Learning Model, Learning Outcomes, and Chemical EquilibriumDOI: 10.23960/jppk.v13.i3.32250